Comprehensive and Integrative Analysis of Two Novel SARS-CoV-2 Entry Associated Proteases CTSB and CTSL in Healthy Individuals and Cancer Patients - Huang, Yongbiao; Li, Shiyu; Huang, Shanshan; Tu, Jingyao; Chen, Xinyi; Xiao, Lingyan; Liu, Bo; Yuan, Xianglin (Frontiers in Bioengineering and Biotechnology, 2022)
More than 200 million people infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and 4 million deaths have been reported worldwide to date. Cathepsin B/Cathepsin L (CTSB/L) are SARS-CoV-2 entry-associated proteases and facilitate SARS-CoV-2 to infect host cells. However, the expressions of CTSB/L in healthy individuals and cancer patients remain not fully elucidated yet. Here, we comprehensively profiled the expression and distribution of CTSB/L in human normal tissues, cancer tissues and cell lines. Moreover, we compared CTSB/L expression between various cancers and matched normal tissues, investigated their genetic alteration and prognostic values in pan-cancer. Finally, we also explored the correlation between CTSB/L expression and immune infiltration. We found that CTSB was highly expressed in most tissues, and CTSL was highly expressed predominantly in digestive, urinary and respiratory systems, such as lung, liver & gallbladder and kidney tissues in the translational level. Moreover, cancer patients may be more susceptible to SARS-CoV-2 infection. Our data suggested that CTSB/L were overexpressed in aerodigestive and genitourinary cancers compared with that in matched normal tissues, and their expression was closely related to the prognosis of some cancer types. Interestingly, CTSB/L expression was significantly correlated with immune cell infiltration in manifold cancer tissues and corresponding normal tissues. In conclusion, our study showed a comprehensive bioinformatic analysis of two important SARS-CoV-2 entry-related proteases, which could provide a potential indication on prevention of SARS-CoV-2 infection.